Aspects of recusant history - Birrell, T. A.; Blom, Jos; Korsten, F. J. M. (Franciscus Johannes Marie); Blom, Frans (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Thomas Anthony Birrell (1924-2011) was a man of many parts. For most of his working life he was Professor of English and American Literature in the University of Nijmegen, The Netherlands, where he was famous for his lively, humoristic and thought-provoking lectures. He was the author of some very popular surveys of English Literature in Dutch, but - first and foremost - he was a bibliographer and a historian. His scholarly oeuvre is extensive and includes such highlights as English Monarchs and their Books (London 1986), a study of the Old Royal Library. However, many of his publications are hidden in occasional publications, periodicals and introductions to books no longer in print. That is why a - posthumous - selection of his bibliographical essays appeared in 2013, entitled Aspects of Book Culture (Ashgate 2013) and that is why it was decided to bring out a companion volume containing a selection of his essays in the field of recusant history. The present edition contains fourteen of Birrell's articles published between 1950 and 2006. They all demonstrate his bibliographical expertise, his in-depth knowledge of seventeenth- and eighteenth-century English catholic history and his absolute determination to examine every scrap of archival material that might shed light on the episodes he was investigating. But, perhaps most important of all, he combined his scholarship with an intense interest in the individual lives that shape and are shaped by history, so the lasting impression that these articles will make is the sense of getting close to a whole series of personalities caught up in the turmoil of their time. Aspects of Recusant History was edited by Jos Blom, Frans Korsten and Frans Blom, all three former students of Tom Birrell"--
OCLC-licensed vendor bibliographic record.
Keywords: Catholic Church -- England -- History; HISTORY / General